Immunohistochemical staining for adipophilin, perilipin and TIP47. Issue 11 (23rd March 2006) - Muthusamy, K; Halbert, G; Roberts, F
Abstract : Background: The presence of lipid in the cell cytoplasm is useful for supporting the diagnosis of sebaceous gland carcinoma (SGC). Currently this requires histochemical stains that are carried out on frozen sections of unprocessed tissue. Recently, several anti-adipocytic antibodies that recognise proteins associated with lipid vesicles have been described. These antibodies can be applied to paraffin-wax sections. Aim: To assess the ability of anti-adipocytic antibodies to identify intracytoplasmic lipid in SGC. Methods: Immunohistochemistry with a monoclonal antibody to adipophilin and polyclonal antibodies to perilipin and TIP47/PP17 was carried out on archival, formalin-fixed, paraffin-wax-embedded sections of 26 samples of SGC. The immunostaining was compared with 22 other eyelid tumours (11 basal cell carcinomas (BCC), 10 squamous cell carcinomas (SCC) and 1 Merkel cell tumour). Results: Immunohistochemical staining was positive in 23, 10 and 2 cases of 26 SGC with adipophilin, perilipin and TIP47, respectively. The positive staining identified cytoplasmic lipid vesicles. Anti-adipophilin was positive in five other eyelid tumours (4 BCC and 1 SCC) staining small cytoplasmic granules that can be easily distinguished from the staining in SGC. Conclusions: Immunohistochemical staining for adipophilin and perilipin is a useful ancillary technique for the demonstration of lipid in SGC that may be applied to paraffin-wax sections.